0646 Sleep Disorders and Sleep Medication Use in Youth with Persistent Tic Disorders. (25th May 2022) - Ricketts, Emily; Qu, Christine; Rissman, Ariel; Swisher, Valerie; Burgess, Helen; Coles, Meredith; Colwell, Christopher; Piacentini, John
Abstract: Introduction: Sleep disturbance is present in 80% of youth with persistent tic disorders (PTD). However, studies examining rates of sleep disorders in youth with PTD are limited, and reports on sleep medication use in this population are lacking. Such knowledge would inform understanding of assessment and treatment needs of youth with PTD. Therefore, the present study examined rates of sleep disorders and sleep medication use among youth with PTD, and their associations with tic severity and ADHD symptoms. Methods: Participants were 52 parents of youth with PTD who responded to an internet survey evaluating sleep-wake patterns. Youth were predominantly male (n = 37, 72.5%); and 88.5% (n = 46) were reported to have Tourette's disorder and 11.5% (n = 6) were reported to have persistent motor tic disorder. Parents provided demographics and medical history, including lifetime sleep disorder diagnosis by a health professional and current prescription or over-the-counter sleep medication use. Parents rated youth tic severity (Parent Tic Questionnaire) and ADHD symptom severity (Swanson, Nolan, and Pelham-IV Parent Rating Scale). Results: Descriptive statistics and independent samples t-tests were performed. Per parent report, 39.2% (n = 20) of youth with PTD had one or more lifetime sleep disorders. Insomnia (n = 9, 17.3%), nightmares (n = 9, 15.7%), sleep walking (n = 5, 10.0%), bruxism (n = 5, 10.0%), and restless leg syndrome (n = 5, 10.0%) were most commonly endorsed. Fifty percent of parents of youth with PTD endorsed youth sleep medication use. The most commonly endorsed sleep medications were melatonin (n = 23, 44.2%), valerian (n = 6, 11.5%), and diphenhydramine (n = 5, 9.6%). There were no significant group differences in tic severity or ADHD symptom severity. Conclusion: Findings highlight the presence of disorders of sleep initiation and maintenance, parasomnias, and sleep-related movement disorders in youth with PTD. Results indicate that sleep medication use, particularly melatonin, is common in this population. Future research is needed to test the efficacy of melatonin use for addressing sleep problems in youth with PTDs. Support (If Any): NIMH K23 MH113884 funding to Dr. Ricketts.